2013
DOI: 10.1111/ene.12332
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of cerebral microbleeds determines their association with arterial stiffness in non‐cardioembolic acute stroke patients

Abstract: Arterial stiffness was independently associated with deep or infratentorial CMBs but not lobar CMBs. These findings suggest a pathophysiological association between arterial stiffness and CMBs in the deep or infratentorial region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 29 publications
(53 reference statements)
4
27
1
1
Order By: Relevance
“…We are aware of several previous studies that examined the association of brachial-ankle or carotid-femoral pulse wave velocity with the presence of CMBs. 10,17,18 Those results based on indirect measures of regional arterial stiffness over a certain arterial length, are consistent with our results. More recently, local carotid stiffness measures have been reported to be associated with larger volume of white matter hyperintensities.…”
Section: Discussionsupporting
confidence: 91%
“…We are aware of several previous studies that examined the association of brachial-ankle or carotid-femoral pulse wave velocity with the presence of CMBs. 10,17,18 Those results based on indirect measures of regional arterial stiffness over a certain arterial length, are consistent with our results. More recently, local carotid stiffness measures have been reported to be associated with larger volume of white matter hyperintensities.…”
Section: Discussionsupporting
confidence: 91%
“…The extent of white-matter hyperintensities was determined on the FLAIR images for the periventricular white matter or deep white matter according to the Fazekas scoring system 12. A Fazekas score of 3 in periventricular white matter or ≥2 in deep white matter was considered to indicate HWHs.…”
Section: Methodsmentioning
confidence: 99%
“…Although it has been shown that microbleeds in the pallidum and putamen are strongly associated with hypertension, the association with aortic stiffening is less obvious. Recent larger studies assessing the association between aortic stiffening and the presence of microbleeds demonstrate a slight association with increased vascular stiffening, 70, 71 although not all studies support this finding. 62, 63 …”
Section: Mri Of Brain Small Vessel Disease and Aortic Functionmentioning
confidence: 97%